Familial Florid Cemento-Osseous Dysplasia: A Rare Manifestation in an Indian Family - Adit Srivastava; Rahul Agarwal; Romesh Soni; Avesh Sachan; G. C. Shivakumar; T. P. Chaturvedi (Case Reports in Dentistry)
Florid cemento-osseous dysplasia (FCOD) is one of the uncommon dysplasias affecting the maxillofacial region. The age group may vary from 19 to 76 years and typically presents in the 4th and 5th decades. In most cases patients do not have hereditary basis of disease, and only a few familial cases have been documented. As far as we know this is the 1st reported case of familial FCOD in an Indian family. The mother and son exhibited multiple sclerotic masses in both jaws. The mode of transmission appeared to be autosomal dominant with variable phenotypic expression.